Nutrition at Early Stages of Life Determines the Future Growth and Reproductive Performance of Dairy Calves - Philipe Moriel; Fernanda Batistel (EDIS)
This fact sheet summarizes some of the research conducted in calf nutrition and nutrition’s impact on the growth and reproductive performance of dairy calves. Written by Philipe Moriel and Fernanda Batistel, and published by the UF/IFAS Department of Animal Sciences, revised November 2021.